Study on Shaping and Activating the Artistic Conception of Garden in "Qin Feng·The Reed" - Tan, Yin; Zhao, Wei; Xing, Fengyu; Wu, Lili (International Journal of Natural Resources and Environmental Studies, 2025)
In recent years, the ‘Qin Feng·The reed’ research in the main idea, word discernment, etc., from the garden point of view of the research is less and there are deficiencies. In this paper, from the garden elements to analyse the ‘Qin Feng·The reed’, to explore the meaning of its garden and the significance of modern garden construction. Analysis of ‘Qin Feng·The reed’ in the plants, water, terrain and other garden elements, to explore its plane, space, seasonal composition and mood creation, research on modern garden space layout, plant configuration and mood creation and other aspects of the revitalisation of the application. ‘Qin Feng·The reed’ contains rich garden aesthetic elements, for modern garden landscape revitalisation to provide inspiration, conducive to the inheritance of culture, promote the development of garden art, the future can be in-depth study of its relationship with the garden, integration of multidisciplinary knowledge innovation.